DEVELOPMENT OF HOTS-BASED EDUCATIONAL MONOPOLY BOARD GAME MEDIA TO IMPROVE STUDENTS' ANALYTICAL ABILITIES IN THE CREED AND MORALS SUBJECT IN GRADE VIII MTsN 3 TUBAN - Karara Dwi krisnaeni; Muslimin Muslimin (Jurnal Bilqolam Pendidikan Islam, 2026)
This research is motivated by the low analytical ability of eighth grade students in the subject of Akidah Akhlak at MTsN 3 Tuban, which is caused by the limited use of Higher Order Thinking Skills (HOTS)-based learning media. The learning process is still dominated by conventional methods causing students to be less active in critical thinking, analyzing problems, and connecting material with everyday life. Therefore, this study aims to produce a HOTS-based educational monopoly board game media that is valid, practical, and effective in improving students' analytical abilities in Akidah Akhlak learning. This study uses the Research and Development (R&D) method with a 4D development model that includes the define, design, develop, and disseminate stages. The research subjects consisted of 28 eighth grade students of MTsN 3 Tuban. Data collection instruments include expert validation sheets, practicality observation sheets, teacher response questionnaires, and pretest and posttest tests. The results showed that the HOTS-based educational monopoly board game media obtained a validity level of 90.4% with a very valid category. The practicality level of the media based on student observations and teacher responses reached 87.3% with a very practical category. Meanwhile, the effectiveness of the media is shown by the increase in the average student score from 64.11 in the pretest to 92.68 in the posttest, with an average N-Gain value of 0.79 which is included in the high category. In addition, all students or 100% of students successfully achieved the Minimum Completion Criteria (KKM) in the posttest. Thus, the HOTS-based educational monopoly board game media is declared feasible and effective for use in improving students' analytical abilities in learning Akidah Akhlak.